INOVASI MANAJEMEN KEPALA MADRASAH DALAM PENGEMBANGAN STANDAR NASIONAL PENDIDIKAN - Sutriasih -; Isytaharo Amroh; Rifqi Muntaqo; Samsul Munir (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2021)
Management innovation needs to be carried out by madrasa heads in developing national education standards. This is important to do in order to create a madrasa that is more qualified and able to adapt to the times. This study uses a qualitative, descriptive approach conducted at MI Ma'arif Bendosari Sapuran Wonosobo and MI Muhammadiyah Leksono Wonosobo using a case study design. The results show that good management will create changes for the better. Improvement for the better occurs through an innovation. Innovation begins with planning, implementation, and sustainability. Innovation works well if there is cohesiveness to form a Super Team. The form of innovation at the research site includes eight standards, namely the competency standard of graduates by graduating students who are Qur'anic and have noble character; content standards by adding additional material according to the wisdom of the madrasa; process standards, namely the existence of standard operating procedures (SOP) for each activity; educational assessment standards, namely the existence of a report card of special characteristics of worship habituation assessment; education personnel standards, namely by involving teachers in education and training as well as further studies as teacher competency development; standard of facilities and infrastructure by procuring buildings and shuttle cars; management standards, namely collaborating with other parties for the advancement of madrasas; and financing standards, one of which is through collaboration with student guardians, and donors for the advancement of madrasas.